Characterization of Haze Particulate Matter - Lau, Tai Meng (2003)
Haze has became a public concern especially after the 1997 haze episode which resulted from large-scale forest fires that caused transboudary spreading of air pollution. Particulate matters are primarily responsible for creating haze in the atmosphere as well as adverse effects on human health. Thus, both of the physical and chemical characteristics of particulate matters are important when attempting to elucidate particle toxicity. Particulate matters, which aerodynamic diameter equal or less than 10µm (PM₁₀ ) were measured in the periods from 1997 to 2000 at UPM station. High volume sampler (HVS) was used to collect most of the ambient particle samples and a small portion was collected using particle counter. Sampling of particulate matter was carried out from various emission sources such as peat swamp fire at Sepang, biomass burning at paddy field and several types of vehicle exhaust. Besides that, simulated peat soil and rice straw burning were also conducted in the fumigation chamber to collect particulate matter. Chemical analysis was performed by atomic absorption spectrophotometer (AAS) to identify ten kind of common trace metals, namely potassium (K), zinc (Zn), magnesium (Mg), sodium (Na), calcium (Ca), iron (Fe), manganese (Mn), lead (Pb), chromium (Cr) and copper (Cu).